Reliability Analysis of Fatigue Crack Growth in Plain Concrete (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Civil engineers know that fatigue indicates themajority of structural failures. In plain and reinforced concrete structures, fatigue might account for excessivedeformation, excessive of crack widths, de-bonding ofreinforcement and rupture of the reinforcement, all of thesecan lead to structural collapse. Fatigue crack propagation can be a method to predict a remaining life of structures.Herein some works that have been done will be shown inorder to analyse the fatigue crack growth for plain concretespecimens. The goals of this study are to estimate the criticalcrack length and remaining life of a plain concrete specimen, determine the state of the specimen either havingfailed or being safe using first order reliability method(FORM) and assess which parameter has most influence onthe reliability index